THERMAL STRESSES IN RIM BRAKE DRUM MOTOR VEHICLES - Бурава, Олександр; Ніщук, Віктор; Малик, Володимир; Федик, Василь; Джавала, Микола (Problems of Friction and Wear, 2022)
In the materials of the article, an assessment of thermal stresses in the rims of brake drums (vehicles) was made, based on their design and thermophysical parameters, as well as the mechanical properties of materials. Thermal stresses in the drum rim due to thermal deformations are considered. In this case, the drum was broken into rings, and the ring was subjected to the study, rimmed with its wall. In order to obtain full thermal stresses, it was necessary to impose stresses caused in the shell by an intensity load. Further, the deformations arising from thermal action along the length of the drum rim are determined. The total stresses included the terms from the action of the surface temperature gradient and the bulk temperature across the thickness of the drum rim. A brake shoe with friction linings and a brake drum is an energy-loaded system in which the brake drum is an energy-intensive unit. The lower volume temperature of the side wall of the brake drum rim is explained by the fact that its outer surface (polished) adjoins the wheel hub and takes part in conductive heat exchange, while the outer (matt) surface is free and is washed by air flows circulating in the cavity of the drum-shoe brake , i.e., takes part in forced convective heat transfer. The removal of heat from the friction surface of the brake drum can be improved by: using metals for its rims with a high thermal conductivity; an increase in the area of ​the outer surface of the drum rim by forced cooling due to fins; improvement of ventilation of working and non-working surfaces of the brake drum. Thermal deformations and stresses of the brake drum rim result from the temperature difference in the radial and axial directions; in addition, they depend on the intensity with which the heat sinks from the rim to the side wall of the drum and further, depending on its thickness. The temperatures of the outer and inner surfaces of the brake drum rim differ slightly. The temperature difference along the generatrix of the rim, i.e., in the axial direction, can be significant, which causes significant thermal deformations and stresses. In this case, the functional dependence of the drum rim temperature on the linear coordinate is determined empirically and can be approximated by some analytical function determined by the temperature distribution graph.